The Influence of Animation and Spatial Augmented Reality Integration on Audience Responses to Immersive Arts. - Auzani Zeda, Mohamed Kassim (International Journal of Latest Technology in Engineering, Management & Applied Science (IJLTEMAS), 2024)
This research examines the integration of animation and Spatial Augmented Reality (SAR) to create immersive artworks in gallery environments. As part of exploring the unexplored domain of SAR-animation convergence, the study looks at the spectators' responses towards this innovative approach in the limited gallery spaces, focusing on viewers' engagement and acceptance. By utilising a combination of research approaches—including audience surveys and creative experiments—the study uncovers the potentials of animation-SAR-based immersive experiences. The results highlight the potential of this growing area, notwithstanding obstacles such as high costs and implementation complexity. The research indicates that immersive art engages viewers to a deeper level and can have an emotional impact; it enriches the viewers' experiences and may contribute as a tool to other significant disciplines, such as art therapy.